Semantic metadata information (SMI) visualisation technique using the integration of ontology and UML graph-based approach to support program comprehension / Rozita Kadar ... [et al.] - Kadar, Rozita; Othman, Jamal; Abdul Wahab, Naemah; Warris, Saiful Nizam (UiTM Cawangan Perlis, 2019)
Representing any ideas with pictures rather than words is intuitively more appealing because a visual presentation can be more readily understood than that of textual-based. Program visualisation is one of the techniques that can be used in teaching to help users in understanding how programs work. Program visualisation technique is a mental image or a visual representation of an object, scene, person or abstraction that is similar to visual perception. This technique is significant to users because the criteria of source code cannot be physically viewed. It is applicable in the process of writing programs as it helps users to understand their codes better. The purpose of program visualisation is to translate a program into a graphical view to show either the program code, data or control flow. Visualisation technique uses the capability of human visual system to enhance program comprehensibility. Thus, this study uses program visualisation technique to represent program domain in a graphical view to help novices in improving their comprehension. This research aims to support beginners or novice programmers who have been exposed to programming languages by providing effective visualisation technique.